Nano modified epoxy building thermal insulation material and preparation method thereof

Through the preparation of nano-modified epoxy building insulation materials, the formation of regular pore structures is achieved by combining polydopamine and loaded aerogels, and the shortcomings of existing materials in insulation performance and toughness are solved. It achieves efficient heat insulation and fire resistance.

CN119430815APending Publication Date: 2025-02-14HUBEI QINGCHENG CONSTR ENG CO LTD
View PDF 0 Cites 7 Cited by

Patent Information

Application Number
CN202411826333.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing building insulation materials have shortcomings in insulation performance and toughness, and the poor compatibility of nano-scale materials during composite affects the composite effect.

Method used

Nanomodified epoxy building insulation materials, whose raw materials include silicate cement, slag powder, hollow mesoporous silica, pyrrole, ammonium persulfate, nano-silica, etc., and are formed through compounding and freezing-thawing cycles. Regular pore structure and combine polydopamine and loaded aerogel to improve the thermal insulation and fire resistance of the material.

Benefits of technology

It significantly improves the compressive strength and thermal insulation performance of building insulation materials, while reducing the bulk weight of the material, enhancing the fireproof effect, and meeting building energy-saving needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430815A_ABST
    Figure CN119430815A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field, and particularly discloses a nano-modified epoxy building thermal insulation material and a preparation method thereof. The nano modified epoxy building thermal insulation material is prepared from the following raw materials in parts by mass: 80 to 120 parts of Portland cement, 20 to 40 parts of slag powder, 5 to 10 parts of hollow mesoporous silicon dioxide, 0.1 to 1 part of pyrrole, 0.1 to 0.2 part of ammonium persulfate, 5 to 10 parts of nano silicon dioxide, 10 to 15 parts of bisphenol S epoxy resin, 1 to 5 parts of acrylic acid, 1 to 2 parts of polylysine, 0.01 to 0.1 part of catalyst and 1 to 2 parts of curing agent. The concrete is prepared from the following raw materials in parts by weight: 20-30 parts of epoxy resin, 4-8 parts of loaded aerogel, 0.1-1 part of polycarboxylate superplasticizer, 1-4 parts of composite fiber and 0.2-1.25 parts of hydrogen peroxide. The fireproof building material has excellent toughness, can better resist cracking and absorb energy, effectively avoids cracking and damage under the action of thermal stress, and ensures that the building material has a fireproof effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field, and in particular to a nano-modified epoxy building thermal insulation material and a preparation method thereof. Background Art

[0002] With the continuous development of social economy and science and technology, people's requirements for building materials have become more prominent, and new building materials have emerged and are constantly innovating in technology. At present, most buildings are high-energy-consuming buildings, and the heat loss caused by poor insulation accounts for a very large proportion. Therefore, the development of energy-saving and thermal insulation materials is of great significance.

[0003] Common thermal insulation materials on the market can be divided into two categories: organic polymer materials and inorganic materials. Organic polymer materials have good toughness, light weight, and high thermal insulation efficiency, but poor flame retardancy, poor aging resistance, and short service life; while the main advantages of inorganic materials are low cost, flame retardancy, and good aging resistance, but they will increase the overall weight of the building and lack toughness.

[0004] After rapid development in recent years, my country's thermal insulation materials have been improved by using nano-scale materials, which effectively enhances the thermal insulation performance and toughness, and may also improve the fire resistance of building materials. However, the composite effect of nano-scale materials is affected due to poor compatibility when composited with other materials. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a nano-modified epoxy building thermal insulation material and a preparation method thereof.

[0006] A nano-modified epoxy building thermal insulation material comprises the following raw materials by mass: 80-120 parts of silicate cement, 20-40 parts of slag powder, 5-10 parts of hollow mesoporous silica, 0.1-1 part of pyrrole, 0.1-0.2 part of ammonium persulfate, 5-10 parts of nano-silica, 10-15 parts of bisphenol S epoxy resin, 1-5 parts of acrylic acid, 1-2 parts of polylysine, 0.01-0.1 parts of catalyst, 1-2 parts of curing agent, 4-8 parts of loaded aerogel, 0.1-1 part of polycarboxylic acid water reducer, 1-4 parts of composite fiber and 0.2-1.25 parts of hydrogen peroxide.

[0007] Preferably, the catalyst is a tertiary amine.

[0008] Preferably, the curing agent is menthane diamine.

[0009] Preferably, the composite fiber includes at least two of glass fiber, basalt fiber, sepiolite fiber and nylon fiber.

[0010] Preferably, the loaded aerogel is prepared by the following steps: adding polyvinyl alcohol, graphene oxide, and octaepoxycyclohexylethyl cage-type polysilsesquioxane to tetrahydrofuran, adjusting the pH value of the system to 7-8, stirring at 60-80°C for 1-2h, adjusting the pH of the system to be neutral, removing tetrahydrofuran by vacuum distillation, adding water and stirring evenly, freezing-thawing cycles for 2-4 times, vacuum drying, immersing in a Tris-HCl buffer solution, adding dopamine for ultrasonic treatment for 2-6h, filtering, washing, and vacuum drying.

[0011] The present invention utilizes octaepoxycyclohexylethyl cage-type polysilsesquioxane in combination with polyvinyl alcohol and graphene oxide, and adopts directional freezing in a freeze-thaw cycle to make the product structure have a regularly arranged pore structure, and polydopamine is combined on its surface to play a spatial barrier role. The amino group on it is combined with the prepolymer to form a large number of closed channels, effectively reduce the convection effect, and improve the thermal insulation performance. On the premise of ensuring light weight, the combustible gas generated by decomposition can be effectively adsorbed, and a stable barrier effect can be played to avoid the generation of more smoke.

[0012] More preferably, the mass ratio of polyvinyl alcohol, graphene oxide, octaepoxycyclohexylethyl cage-type polysilsesquioxane, and dopamine is 5-10:1-2:1-3:1-2.

[0013] More preferably, during the freeze-thaw cycle, a bottom cold plate directional freezing is adopted, and the freezing temperature is -30 to -40°C.

[0014] More preferably, the pH value of the Tris-HCl buffer solution is 7.5-8.

[0015] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0016] S1. Add hollow mesoporous silica and pyrrole to aniline solution and ultrasonically treat for 1-2 hours, add ammonium persulfate thereto, continue ultrasonically treating for 10-30 minutes, let stand for 10-20 hours, filter, wash, and freeze-dry to obtain enhanced silica;

[0017] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding silicate cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0018] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, a catalyst and a curing agent are added thereto, and the mixture is stirred at 60-80° C. for 10-30 minutes to obtain a prepolymer;

[0019] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber and water to the prepolymer and stirring for 10-20 seconds, adding premixed cementitious base thereto and stirring for 10-20 seconds, and then adding water and stirring for 1-2 minutes to obtain slurry;

[0020] S5. Add hydrogen peroxide solution to the slurry, stir for 3-6 seconds, put it into the mold for foaming, naturally cure for 5-10 days, dry at 80-90℃ for 1-2 hours, and cool to room temperature.

[0021] Preferably, in S1, the ultrasonic frequency is 2-6 kHz.

[0022] Beneficial effects:

[0023] The present invention in situ grows a structure of polyaniline nanofibers and polypyrrole doped with each other inside and outside the hollow mesoporous silica, and then compounds with nano-silica to modify cement, which can significantly improve the mechanical properties of cement-based materials. In combination with the effect of high molecular prepolymers, the compressive strength of the thermal insulation material is improved while ensuring the thermal conductivity of the thermal insulation material and effectively reducing the bulk density of the product. Further compounding with loaded aerogel and foaming technology not only makes the material have a large number of pores, but also contains a large number of regular closed channels, which significantly improves the thermal insulation performance of the material, meets the needs of construction, and can be used as an energy-saving exterior wall thermal insulation material for buildings.

[0024] The present invention utilizes prepolymer, loaded aerogel and premixed cement to form a composite, which can not only effectively adhere to the hydration product of the cementitious material to form a certain polymer film, but also form a continuous polymer network and a porous structure, which can significantly improve the structural morphology of the material. The thermal insulation material not only has excellent thermal insulation performance, but also has good mechanical properties and low water absorption. The two-dimensional graphene structure distributed in the loaded aerogel cooperates with the ordered structure of the reinforced silica, which not only enhances the ability of the thermal insulation material to resist heat damage, but also effectively slows down the spread of fire, and has excellent fire prevention effect.

[0025] The present invention has excellent toughness, can better resist cracking and absorb energy, effectively avoids cracking and damage under thermal stress, ensures that the building material has a fireproof effect, thereby better meeting the requirements of building materials and having broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison chart of the compressive strength and thermal conductivity of the thermal insulation materials obtained in Example 5 and Comparative Examples 1-3.

[0027] Figure 2 It is a comparison chart of the dry apparent density and volume water absorption rate of the thermal insulation materials obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0028] The present invention will be further explained below in conjunction with specific embodiments.

[0029] Example 1

[0030] A nano-modified epoxy building thermal insulation material, whose raw materials include: 800g of 42.5-grade ordinary Portland cement, 200g of slag powder, 50g of hollow mesoporous silica, 1g of pyrrole, 1g of ammonium persulfate, 50g of nano-silica, 100g of bisphenol S epoxy resin, 10g of acrylic acid, 10g of polylysine, 0.1g of tertiary amine, 10g of menthane diamine, 40g of loaded aerogel, 1g of polycarboxylic acid water reducer, 10g of composite fiber and 2g of hydrogen peroxide.

[0031] The composite fiber is composed of glass fiber and sepiolite fiber in a mass ratio of 2:1.

[0032] The loaded aerogel is prepared by the following steps: 5g of polyvinyl alcohol, 1g of graphene oxide, and 1g of octaepoxycyclohexylethyl cage-type polysilsesquioxane are added to 20g of tetrahydrofuran, and the pH value of the system is adjusted to 7-8 with a sodium hydroxide solution with a concentration of 1 mol / L, and stirred at a temperature of 60°C for 1h. The system is adjusted to be neutral with hydrochloric acid, and the tetrahydrofuran is removed by vacuum distillation, 50g of water is added and stirred evenly, and the aerogel is subjected to freeze-thaw cycle treatment twice, wherein the freezing process is directionally frozen on a bottom cold plate at a temperature of -30°C, vacuum dried, immersed in 30g of Tris-HCl buffer solution with a pH of 7.5-8, 1g of dopamine is added, and ultrasonic treatment is performed for 2h at an ultrasonic frequency of 2kHz, filtered, washed, and vacuum dried.

[0033] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0034] S1. Add hollow mesoporous silica and pyrrole to 200 g of aniline solution with a concentration of 0.5 g / L, perform ultrasonic treatment for 1 h at an ultrasonic frequency of 2 kHz, add ammonium persulfate thereto, perform ultrasonic treatment for 10 min, let stand for 10 h, filter, wash, and freeze-dry to obtain enhanced silica;

[0035] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0036] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 60° C. for 10 minutes to obtain a prepolymer;

[0037] S4, adding the loaded aerogel, polycarboxylate water reducer, composite fiber, and 100 g of water to the prepolymer and stirring for 10 s, adding the premixed cementitious base thereto and stirring for 10 s, and then adding 100 g of water and stirring for 1 min to obtain a slurry;

[0038] S5. Add 20% by mass aqueous hydrogen peroxide solution to the slurry, stir for 3 seconds, put it into a mold for foaming, naturally cure for 5 days, dry it at 80°C for 1 hour, and cool it to room temperature.

[0039] Example 2

[0040] A nano-modified epoxy building thermal insulation material, whose raw materials include: 1200g of 42.5-grade ordinary Portland cement, 400g of slag powder, 100g of hollow mesoporous silica, 10g of pyrrole, 2g of ammonium persulfate, 100g of nano-silica, 150g of bisphenol S epoxy resin, 50g of acrylic acid, 20g of polylysine, 1g of tertiary amine, 20g of menthane diamine, 80g of loaded aerogel, 10g of polycarboxylic acid water reducer, 40g of composite fiber and 12.5g of hydrogen peroxide.

[0041] The composite fiber is composed of glass fiber and basalt fiber in a mass ratio of 3:2.

[0042] The loaded aerogel is prepared by the following steps: 10g of polyvinyl alcohol, 2g of graphene oxide, and 3g of octaepoxycyclohexylethyl cage-type polysilsesquioxane are added to 30g of tetrahydrofuran, a 2mol / L sodium hydroxide solution is used to adjust the pH value of the system to 7-8, stirring at a temperature of 80°C for 2h, hydrochloric acid is used to adjust the system to be neutral, tetrahydrofuran is removed by vacuum distillation, 100g of water is added and stirred evenly, and a freeze-thaw cycle is performed for 4 times, wherein the freezing process is directionally frozen on a bottom cold plate at a temperature of -40°C, vacuum dried, immersed in 60g of Tris-HCl buffer solution with a pH of 7.5-8, 2g of dopamine is added for ultrasonic treatment for 6h, the ultrasonic frequency is 8kHz, filtered, washed, and vacuum dried.

[0043] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0044] S1. Add hollow mesoporous silica and pyrrole to 400 g of aniline solution with a concentration of 1 g / L, perform ultrasonic treatment for 2 h at an ultrasonic frequency of 6 kHz, add ammonium persulfate thereto, perform ultrasonic treatment for 30 min, let stand for 20 h, filter, wash, and freeze-dry to obtain enhanced silica;

[0045] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0046] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 80° C. for 30 minutes to obtain a prepolymer;

[0047] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 200 g of water to the prepolymer and stirring for 20 seconds, adding premixed cementitious base thereto and stirring for 20 seconds, and then adding 200 g of water and stirring for 2 minutes to obtain slurry;

[0048] S5. Add 25% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 6 seconds, put it into a mold for foaming, naturally cure for 10 days, dry it at 90°C for 2 hours, and cool it to room temperature.

[0049] Example 3

[0050] A nano-modified epoxy building thermal insulation material, whose raw materials include: 900g of 42.5-grade ordinary Portland cement, 350g of slag powder, 70g of hollow mesoporous silica, 7g of pyrrole, 1.2g of ammonium persulfate, 90g of nano-silica, 110g of bisphenol S epoxy resin, 40g of acrylic acid, 13g of polylysine, 0.7g of tertiary amine, 13g of menthane diamine, 70g of loaded aerogel, 3g of polycarboxylic acid water reducer, 30g of composite fiber and 5g of hydrogen peroxide.

[0051] The composite fiber is composed of basalt fiber, sepiolite fiber and nylon fiber in a mass ratio of 2:1:5.

[0052] The loaded aerogel was prepared by the following steps: 9 g of polyvinyl alcohol, 1.3 g of graphene oxide, and 2.5 g of octa-epoxycyclohexylethyl cage-type polysilsesquioxane were added to 22 g of tetrahydrofuran, the pH value of the system was adjusted to 7-8 with a sodium hydroxide solution having a concentration of 1.7 mol / L, and the mixture was stirred at a temperature of 65°C for 100 min. Hydrochloric acid was used to adjust the system to be neutral, and the tetrahydrofuran was removed by vacuum distillation, 70 g of water was added and stirred evenly, and the mixture was subjected to freeze-thaw cycle treatment for 3 times, wherein the mixture was directionally frozen on a bottom cold plate at a temperature of -38°C during the freezing process, vacuum dried, immersed in 40 g of a Tris-HCl buffer solution with a pH of 7.5-8, 1.7 g of dopamine was added, and the mixture was ultrasonically treated for 3 h at an ultrasonic frequency of 7 kHz, filtered, washed, and vacuum dried.

[0053] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0054] S1, adding hollow mesoporous silica and pyrrole to 260g of aniline solution with a concentration of 0.9g / L, ultrasonically treating for 80min at an ultrasonic frequency of 5kHz, adding ammonium persulfate thereto, ultrasonically treating for 15min, standing for 18h, filtering, washing, and freeze-drying to obtain reinforced silica;

[0055] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0056] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 65° C. for 25 minutes to obtain a prepolymer;

[0057] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 120 g of water to the prepolymer and stirring for 18 s, adding premixed cementitious base thereto and stirring for 13 s, and then adding 170 g of water and stirring for 1.5 min to obtain slurry;

[0058] S5. Add 21% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 5 seconds, put it into a mold for foaming, naturally cure for 7 days, dry it at 88°C for 80 minutes, and cool it to room temperature.

[0059] Example 4

[0060] A nano-modified epoxy building thermal insulation material, the raw materials of which include: 1100g of 42.5-grade ordinary Portland cement, 250g of slag powder, 90g of hollow mesoporous silica, 3g of pyrrole, 1.8g of ammonium persulfate, 70g of nano-silica, 130g of bisphenol S epoxy resin, 20g of acrylic acid, 17g of polylysine, 0.3g of tertiary amine, 17g of menthane diamine, 50g of loaded aerogel, 7g of polycarboxylic acid water reducer, 20g of composite fiber and 10g of hydrogen peroxide.

[0061] The composite fiber is composed of glass fiber and nylon fiber in a mass ratio of 2:5.

[0062] The loaded aerogel was prepared by the following steps: 7 g of polyvinyl alcohol, 1.7 g of graphene oxide, and 1.5 g of octa-epoxycyclohexylethyl cage-type polysilsesquioxane were added to 28 g of tetrahydrofuran, the pH value of the system was adjusted to 7-8 with a sodium hydroxide solution having a concentration of 1.3 mol / L, and the system was stirred at a temperature of 75°C for 80 min. Hydrochloric acid was used to adjust the system to be neutral, and the tetrahydrofuran was removed by vacuum distillation, 90 g of water was added and stirred evenly, and the aerogel was subjected to freeze-thaw cycle treatment for 3 times, wherein the freezing process was directionally frozen on a bottom cold plate at a temperature of -33°C, vacuum dried, immersed in 50 g of Tris-HCl buffer solution with a pH of 7.5-8, 1.3 g of dopamine was added, and the system was ultrasonically treated for 5 h at an ultrasonic frequency of 3 kHz, filtered, washed, and vacuum dried.

[0063] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0064] S1, adding hollow mesoporous silica and pyrrole to 340 g of aniline solution with a concentration of 0.7 g / L, ultrasonically treating for 100 min at an ultrasonic frequency of 3 kHz, adding ammonium persulfate thereto, ultrasonically treating for 25 min, standing for 12 h, filtering, washing, and freeze-drying to obtain reinforced silica;

[0065] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0066] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 75° C. for 15 minutes to obtain a prepolymer;

[0067] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 180 g of water to the prepolymer and stirring for 12 s, adding premixed cementitious base thereto and stirring for 17 s, and then adding 130 g of water and stirring for 1.5 min to obtain slurry;

[0068] S5. Add 23% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 4 seconds, put it into a mold for foaming, naturally cure for 9 days, dry it at 82°C for 100 minutes, and cool it to room temperature.

[0069] Example 5

[0070] A nano-modified epoxy building thermal insulation material, whose raw materials include: 1000g of 42.5-grade ordinary Portland cement, 300g of slag powder, 80g of hollow mesoporous silica, 5g of pyrrole, 1.5g of ammonium persulfate, 80g of nano-silica, 120g of bisphenol S epoxy resin, 30g of acrylic acid, 15g of polylysine, 0.5g of tertiary amine, 15g of menthane diamine, 60g of loaded aerogel, 5g of polycarboxylic acid water reducer, 25g of composite fiber and 8g of hydrogen peroxide.

[0071] The composite fiber is composed of glass fiber, basalt fiber, sepiolite fiber and nylon fiber in a mass ratio of 2:1:3:4.

[0072] The loaded aerogel is prepared by the following steps: 8g of polyvinyl alcohol, 1.5g of graphene oxide, and 2g of octaepoxycyclohexylethyl cage-type polysilsesquioxane are added to 25g of tetrahydrofuran, and the pH value of the system is adjusted to 7-8 with a sodium hydroxide solution with a concentration of 1.5mol / L, and stirred at a temperature of 70°C for 90min. The system is adjusted to be neutral with hydrochloric acid, and the tetrahydrofuran is removed by vacuum distillation, 80g of water is added and stirred evenly, and the aerogel is subjected to freeze-thaw cycle treatment for 3 times, wherein the freezing process is directionally frozen on a bottom cold plate at a temperature of -35°C, vacuum dried, immersed in 45g of Tris-HCl buffer solution with a pH of 7.5-8, 1.5g of dopamine is added, and ultrasonic treatment is performed for 4h at an ultrasonic frequency of 6kHz, filtered, washed, and vacuum dried.

[0073] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0074] S1. Add hollow mesoporous silica and pyrrole to 300 g of aniline solution with a concentration of 0.8 g / L, ultrasonically treat for 90 min at an ultrasonic frequency of 4.5 kHz, add ammonium persulfate thereto, ultrasonically treat for 20 min, let stand for 15 h, filter, wash, and freeze-dry to obtain reinforced silica;

[0075] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0076] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 70° C. for 20 minutes to obtain a prepolymer;

[0077] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 150 g of water to the prepolymer and stirring for 15 seconds, adding premixed cementitious base thereto and stirring for 15 seconds, and then adding 150 g of water and stirring for 1.5 minutes to obtain slurry;

[0078] S5. Add 22% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 5 seconds, put it into a mold for foaming, naturally cure for 8 days, dry it at 85°C for 90 minutes, and cool it to room temperature.

[0079] Comparative Example 1

[0080] A nano-modified epoxy building thermal insulation material, whose raw materials include: 1000g of 42.5-grade ordinary Portland cement, 300g of slag powder, 80g of hollow mesoporous silica, 5g of pyrrole, 1.5g of ammonium persulfate, 80g of nano-silica, 120g of bisphenol S epoxy resin, 30g of acrylic acid, 15g of polylysine, 0.5g of tertiary amine, 15g of menthane diamine, 60g of loaded aerogel, 5g of polycarboxylic acid water reducer, 25g of composite fiber and 8g of hydrogen peroxide.

[0081] The composite fiber is composed of glass fiber, basalt fiber, sepiolite fiber and nylon fiber in a mass ratio of 2:1:3:4.

[0082] The loaded aerogel is prepared by the following steps: 8g of polyvinyl alcohol, 1.5g of graphene oxide, and 2g of octaepoxycyclohexylethyl cage-type polysilsesquioxane are added to 25g of tetrahydrofuran, and the pH value of the system is adjusted to 7-8 with a sodium hydroxide solution with a concentration of 1.5mol / L, and stirred at a temperature of 70°C for 90min. The system is adjusted to be neutral with hydrochloric acid, and the tetrahydrofuran is removed by vacuum distillation, 80g of water is added and stirred evenly, and the aerogel is subjected to freeze-thaw cycle treatment for 3 times, wherein the freezing process is directionally frozen on a bottom cold plate at a temperature of -35°C, vacuum dried, immersed in 45g of Tris-HCl buffer solution with a pH of 7.5-8, 1.5g of dopamine is added, and ultrasonic treatment is performed for 4h at an ultrasonic frequency of 6kHz, filtered, washed, and vacuum dried.

[0083] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0084] S1, adding pyrrole to 300g of aniline solution with a concentration of 0.8g / L, ultrasonically treating for 90min at an ultrasonic frequency of 4.5kHz, adding ammonium persulfate thereto, ultrasonically treating for 20min, standing for 15h, adding hollow mesoporous silica and mixing evenly, filtering, washing, and freeze-drying to obtain reinforced silica;

[0085] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0086] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 70° C. for 20 minutes to obtain a prepolymer;

[0087] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 150 g of water to the prepolymer and stirring for 15 seconds, adding premixed cementitious base thereto and stirring for 15 seconds, and then adding 150 g of water and stirring for 1.5 minutes to obtain slurry;

[0088] S5. Add 22% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 5 seconds, put it into a mold for foaming, naturally cure for 8 days, dry it at 85°C for 90 minutes, and cool it to room temperature.

[0089] Comparative Example 2

[0090] A nano-modified epoxy building thermal insulation material, whose raw materials include: 1000g of 42.5-grade ordinary Portland cement, 300g of slag powder, 80g of hollow mesoporous silica, 5g of pyrrole, 1.5g of ammonium persulfate, 80g of nano-silica, 120g of bisphenol S epoxy resin, 30g of acrylic acid, 15g of polylysine, 0.5g of tertiary amine, 15g of menthane diamine, 60g of loaded aerogel, 5g of polycarboxylic acid water reducer, 25g of composite fiber and 8g of hydrogen peroxide.

[0091] The composite fiber is composed of glass fiber, basalt fiber, sepiolite fiber and nylon fiber in a mass ratio of 2:1:3:4.

[0092] The loaded aerogel is prepared by the following steps: 8g of polyvinyl alcohol, 1.5g of graphene oxide, and 2g of octaepoxycyclohexylethyl cage-type polysilsesquioxane are added to 25g of tetrahydrofuran, and the pH value of the system is adjusted to 7-8 with a sodium hydroxide solution with a concentration of 1.5mol / L, and stirred at a temperature of 70°C for 90min. Hydrochloric acid is used to adjust the system to be neutral, and tetrahydrofuran is removed by vacuum distillation, 80g of water is added and stirred evenly, and the aerogel is subjected to freeze-thaw cycle treatment for 3 times, wherein a four-week freezing method is adopted during the freezing process, the freezing temperature is -35°C, vacuum drying, immersion in 45g of Tris-HCl buffer solution with a pH of 7.5-8, 1.5g of dopamine is added, and ultrasonic treatment is performed for 4h at an ultrasonic frequency of 6kHz, filtering, washing, and vacuum drying.

[0093] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0094] S1. Add hollow mesoporous silica and pyrrole to 300 g of aniline solution with a concentration of 0.8 g / L, ultrasonically treat for 90 min at an ultrasonic frequency of 4.5 kHz, add ammonium persulfate thereto, ultrasonically treat for 20 min, let stand for 15 h, filter, wash, and freeze-dry to obtain reinforced silica;

[0095] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0096] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 70° C. for 20 minutes to obtain a prepolymer;

[0097] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 150 g of water to the prepolymer and stirring for 15 seconds, adding premixed cementitious base thereto and stirring for 15 seconds, and then adding 150 g of water and stirring for 1.5 minutes to obtain slurry;

[0098] S5. Add 22% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 5 seconds, put it into a mold for foaming, naturally cure for 8 days, dry it at 85°C for 90 minutes, and cool it to room temperature.

[0099] Comparative Example 3

[0100] A nano-modified epoxy building thermal insulation material, whose raw materials include: 1000g of 42.5-grade ordinary Portland cement, 300g of slag powder, 80g of hollow mesoporous silica, 5g of pyrrole, 1.5g of ammonium persulfate, 80g of nano-silica, 120g of bisphenol S epoxy resin, 30g of acrylic acid, 15g of polylysine, 0.5g of tertiary amine, 15g of menthane diamine, 60g of loaded aerogel, 5g of polycarboxylic acid water reducer, 25g of composite fiber and 8g of hydrogen peroxide.

[0101] The composite fiber is composed of glass fiber, basalt fiber, sepiolite fiber and nylon fiber in a mass ratio of 2:1:3:4.

[0102] The loaded aerogel was prepared by the following steps: 8 g of polyvinyl alcohol, 1.5 g of graphene oxide, and 2 g of octaepoxycyclohexylethyl cage-type polysilsesquioxane were added to 25 g of tetrahydrofuran, the pH value of the system was adjusted to 7-8 with a 1.5 mol / L sodium hydroxide solution, and the mixture was stirred at 70°C for 90 min. Hydrochloric acid was used to adjust the system to be neutral, and the tetrahydrofuran was removed by vacuum distillation. 80 g of water was added and stirred evenly, and the mixture was subjected to freeze-thaw cycle treatment for 3 times, wherein the freezing process was performed with a bottom cold plate at a temperature of -35°C for direction freezing, and the mixture was vacuum dried.

[0103] The preparation method of the above-mentioned nano-modified epoxy building thermal insulation material comprises the following steps:

[0104] S1. Add hollow mesoporous silica and pyrrole to 300 g of aniline solution with a concentration of 0.8 g / L, ultrasonically treat for 90 min at an ultrasonic frequency of 4.5 kHz, add ammonium persulfate thereto, ultrasonically treat for 20 min, let stand for 15 h, filter, wash, and freeze-dry to obtain reinforced silica;

[0105] S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding 42.5 grade ordinary Portland cement and slag powder thereto and mixing uniformly to obtain a premixed cement base;

[0106] S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, tertiary amine and menthane diamine are added thereto, and stirred at a temperature of 70° C. for 20 minutes to obtain a prepolymer;

[0107] S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber, and 150 g of water to the prepolymer and stirring for 15 seconds, adding premixed cementitious base thereto and stirring for 15 seconds, and then adding 150 g of water and stirring for 1.5 minutes to obtain slurry;

[0108] S5. Add 22% by mass of hydrogen peroxide aqueous solution to the slurry, stir for 5 seconds, put it into a mold for foaming, naturally cure for 8 days, dry it at 85°C for 90 minutes, and cool it to room temperature.

[0109] The compressive strength, thermal conductivity, dry apparent density and volume water absorption of the thermal insulation materials obtained in Example 5 and Comparative Examples 1-3 were measured with reference to JC / T 2357-2016 "Test Methods for Performance of Foam Concrete Products".

[0110] like Figure 1 and Figure 2 As shown, the compressive strength of the thermal insulation material obtained in Example 5 is the highest, while the thermal conductivity, dry apparent density and volume water absorption are the lowest, all of which are better than those of Comparative Examples 1-3 (P < 0.05).

[0111] The combustion performance grades of the thermal insulation materials obtained in Example 5 and Comparative Examples 1-3 were evaluated with reference to GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products".

[0112] The combustion performance grade of the thermal insulation materials obtained in Example 5 and Comparative Examples 1-2 is both Class A, while the combustion performance grade of the thermal insulation material obtained in Comparative Example 3 is Class B1.

[0113] The applicant believes that the reason for the above results is that the present invention utilizes octaepoxycyclohexylethyl cage-type polysilsesquioxane in combination with polyvinyl alcohol and graphene oxide, and adopts directional freezing in the freeze-thaw cycle to make the product structure have a regularly arranged pore structure, and combines polydopamine on its surface to play a spatial barrier role. The amino group on it combines with the prepolymer to form a large number of closed channels, effectively reduce convection and improve thermal insulation performance, and can effectively adsorb the combustible gas produced by decomposition while ensuring light weight, play a stable barrier role, and avoid the generation of more smoke. The present invention also in-situ grows a structure of polyaniline nanofibers and polypyrrole doped with each other inside and outside the hollow mesoporous silica, and then compounds with nano-silica to modify cement, which can significantly improve the mechanical properties of cement-based materials. In combination with the effect of high molecular prepolymers, the compressive strength of the thermal insulation material is improved while ensuring the thermal conductivity of the thermal insulation material and effectively reducing the bulk density of the product. The material is further compounded with loaded aerogel and foaming technology, so that the material not only has a large number of pores, but also contains a large number of regular closed channels, which significantly improves the thermal insulation performance of the material, meets the needs of construction, and can be used as an energy-saving exterior wall thermal insulation material for buildings. The present invention utilizes prepolymer, loaded aerogel and premixed cement to form a composite, which can not only effectively adhere to the hydration product of the cementitious material to form a certain polymer film, but also form a continuous polymer network and a porous structure, which can significantly improve the structural morphology of the material. The thermal insulation material not only has excellent thermal insulation performance, but also has good mechanical properties and low water absorption. The two-dimensional graphene structure distributed in the loaded aerogel cooperates with the ordered structure of the reinforced silica, which not only enhances the ability of the thermal insulation material to resist heat damage, but also effectively slows down the spread of fire, and has excellent fire prevention effect.

[0114] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A nano-modified epoxy building thermal insulation material, characterized in that: The raw materials include, by mass, 80-120 parts of silicate cement, 20-40 parts of slag powder, 5-10 parts of hollow mesoporous silica, 0.1-1 parts of pyrrole, 0.1-0.2 parts of ammonium persulfate, 5-10 parts of nano silicon dioxide, 10-15 parts of bisphenol S epoxy resin, 1-5 parts of acrylic acid, 1-2 parts of polylysine, 0.01-0.1 parts of catalyst, 1-2 parts of curing agent, 4-8 parts of loaded aerogel, 0.1-1 parts of polycarboxylic acid water reducer, 1-4 parts of composite fiber and 0.2-1.25 parts of hydrogen peroxide.

2. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The catalyst is a tertiary amine.

3. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The curing agent is menthane diamine.

4. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The composite fiber includes at least two of glass fiber, basalt fiber, sepiolite fiber and nylon fiber.

5. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The loaded aerogel is prepared by the following steps: adding polyvinyl alcohol, graphene oxide, and octaepoxycyclohexylethyl cage-type polysilsesquioxane to tetrahydrofuran, adjusting the pH value of the system to 7-8, stirring at 60-80°C for 1-2 hours, adjusting the pH of the system to be neutral, removing tetrahydrofuran by vacuum distillation, adding water and stirring evenly, freezing-thawing cycles for 2-4 times, vacuum drying, immersing in a Tris-HCl buffer solution, adding dopamine for ultrasonic treatment for 2-6 hours, filtering, washing, and vacuum drying.

6. The nano-modified epoxy building thermal insulation material according to claim 5, characterized in that: The mass ratio of polyvinyl alcohol, graphene oxide, octaepoxycyclohexylethyl cage-type polysilsesquioxane and dopamine is 5-10:1-2:1-3:1-2.

7. The nano-modified epoxy building thermal insulation material according to claim 5, characterized in that: During the freeze-thaw cycle, the bottom cold plate is used for directional freezing, and the freezing temperature is -30 to -40°C.

8. The nano-modified epoxy building thermal insulation material according to claim 5, characterized in that: The pH value of Tris-HCl buffer solution is 7.5-8.

9. A method for preparing the nano-modified epoxy building thermal insulation material according to any one of claims 1 to 8, characterized in that: The steps include: S1. Add hollow mesoporous silica and pyrrole to aniline solution and ultrasonically treat for 1-2 hours, add ammonium persulfate thereto, continue ultrasonically treating for 10-30 minutes, let stand for 10-20 hours, filter, wash, and freeze-dry to obtain enhanced silica; S2, mixing nano silicon dioxide and reinforced silicon dioxide uniformly, adding silicate cement and slag powder thereto and mixing uniformly to obtain a premixed cement base; S3, bisphenol S epoxy resin, acrylic acid, and polylysine are uniformly mixed, a catalyst and a curing agent are added thereto, and the mixture is stirred at 60-80° C. for 10-30 minutes to obtain a prepolymer; S4, adding loaded aerogel, polycarboxylate water reducer, composite fiber and water to the prepolymer and stirring for 10-20 seconds, adding premixed cementitious base thereto and stirring for 10-20 seconds, and then adding water and stirring for 1-2 minutes to obtain slurry; S5. Add hydrogen peroxide solution to the slurry, stir for 3-6 seconds, put it into the mold for foaming, naturally cure for 5-10 days, dry at 80-90℃ for 1-2 hours, and cool to room temperature.

10. The method for preparing the nano-modified epoxy building thermal insulation material according to claim 9, characterized in that: In S1, the ultrasound frequency is 2-6kHz.

Citation Information

Cited By

  • Nano modified epoxy building thermal insulation material and preparation method thereof

    CN119798929A

  • Preparation method of biomass reinforced cement-based thermal insulation wall material and wall material

    CN120903895A

  • Inorganic coal-friendly grouting material and preparation method thereof

    CN121202512A

  • Inorganic coal-adhesive grouting material and preparation method thereof

    CN121202512B

  • Method for rapidly repairing mass concrete cracks in high-salt and high-humidity environment

    CN121537225A